Minat berkoperasi pada generasi z di era society 5.0 - Khuluddiyah, Zulaikhatul (Maliki Interdisciplinary Journal, 2023)
At present, the world has entered the era of Society 5.0, where the internet is currently and can reach all ages, especially Generation Z. While most cooperatives in Indonesia are still operating manually, only a tiny number have switched to digital. The purpose of this study is to find out how much interest there is in cooperatives among Generation Z in the Society 5.0 era. This research is based on scientific work review methods. Where the author uses a systematic approach to evaluate the contents of book chapters or journal articles. The author analyzes the structure, methodology, findings, and conclusions of the sources reviewed. The results of this study indicate that Generation Z’s interest in cooperatives is still very low, which is influenced by several factors. One of them is trust and convenience. Generation Z tends to prefer other business entities, such as banks, because they can provide all-digital facilities and services and provide better security guarantees when compared to cooperatives. This is a strong reason for cooperatives in Indonesia to develop more and switch to digital.